Periclimenaeus denticulodigitus sp. nov. (Crustacea: Decapoda: Palaemonidae: Pontoniinae), from Heron Island, Queensland, Australia - Bruce, A. J. (Zootaxa, 2014)
An unusual species of the genus Periclimenaeus Borradaile, 1915 (Crustacea: Decapoda: Palaemonidae Pontoniinae) from Heron Island, Queensland, Australia, collected by Dr Niel Bruce in 1979, is described and illustrated. Periclimenaeus denticulodigitus sp. nov., an ascidian associate was collected from coral reef at 7.0 m and presents some interesting new features. It increases to 17 the number of Periclimenaeus known from Heron Island, Queensland, and to 28 the number of species known from Australia. The new species has the second pereiopod fingers minutely denticulate and unique to the genus.